2019
DOI: 10.1155/2019/4783514
|View full text |Cite
|
Sign up to set email alerts
|

Degassing and Cycling of Mercury at Nisyros Volcano (Greece)

Abstract: Nisyros Island (Greece) is an active volcano hosting a high-enthalpy geothermal system. During June 2013, an extensive survey on Hg concentrations in different matrices (fumarolic fluids, atmosphere, soils, and plants) was carried out at the Lakki Plain, an intracaldera area affected by widespread soil and fumarolic degassing. Concentrations of gaseous elemental mercury (GEM), together with H2S and CO2, were simultaneously measured in both the fumarolic emissions and the atmosphere around them. At the same tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…3 indicate that there is no hazard posed by CO 2 and H 2 S outside the crater, as well as no serious conditions are expected to occur within it, considering the present-day volcanic degassing. Our simulated averaged concentrations result to be lower than those reported in the literature for the same investigated area (see Gagliano et al, 2019), and are in very good agreement with the instantaneous concentrations acquired during the April-June 2023 (Fig. 2b; Table 2) and the CO 2 concentration time-series measured by the gas sensors during the gas survey (Supplementary Information).…”
Section: Analysis Of the Probabilistic Gas Dispersion And Health Impactssupporting
confidence: 89%
“…3 indicate that there is no hazard posed by CO 2 and H 2 S outside the crater, as well as no serious conditions are expected to occur within it, considering the present-day volcanic degassing. Our simulated averaged concentrations result to be lower than those reported in the literature for the same investigated area (see Gagliano et al, 2019), and are in very good agreement with the instantaneous concentrations acquired during the April-June 2023 (Fig. 2b; Table 2) and the CO 2 concentration time-series measured by the gas sensors during the gas survey (Supplementary Information).…”
Section: Analysis Of the Probabilistic Gas Dispersion And Health Impactssupporting
confidence: 89%
“…Most previous estimations of Hg flux from volcanic systems have been obtained through the monitoring of SO 2 fluxes and the Hg/SO 2 ratio measured in the volcanic plume. ,, Hg flux from fumaroles has more often been estimated based on the Hg/CO 2 ratio and monitored CO 2 fluxes in the fumarole plume. , Some studies directly measured the Hg flux using field flux chambers . Compared to previously reported Hg emissions from geothermal sources, the estimated emission flux from Karapiti is higher than Hg fluxes measured at La Fossa crater of Vulcano, Italy (4.4–7.1 kg year –1 ), and Nisyros, Greece (0.7 kg year –1 ), similar to Hg fluxes at Tatun volcanic field, Taiwan (5–50 kg year –1 ), and Yellowstone caldera (15–56 kg year –1 ), while much smaller than Hg fluxes at Mount Etna (5.4 t year –1 ) and Masaya volcano, Nicaragua (7.2 t year –1 ) . The large range reflects the complexity in determining the Hg fluxes from geothermal sources, which is affected by many factors such as the physical nature of degassing (i.e., temporal and spatial variability), the temperature of the geothermal activities, and the mineralogical composition of the underlying area.…”
Section: Resultsmentioning
confidence: 99%
“…Mercury is emitted into the atmosphere from both natural and anthropogenic sources, though the exact proportion of each continues to be debated. , Natural sources include the contribution from primary natural sources (e.g., volcanoes) and re-emissions of previously deposited Hg over land and sea surfaces . Degassing volcanoes, fumaroles, and geothermal fields can emit significant amounts of Hg and are perhaps the most important natural Hg sources as they represent a geological input of Hg into the active biogeochemical cycle of Hg at or above the Earth’s surface. Mercury fluxes from volcanoes and geothermal sources, which are predominantly in the form of GEM (>98%), , are estimated to contribute substantially to the total natural Hg flux to the atmosphere both on a global and a regional scale. ,, Two recent reviews estimated a global Hg emission flux from volcanoes to be 90 and 700 t year –1 , another study reported a global Hg flux from degassing volcanoes of 76 ± 30 t year –1 , and a global GEM flux from hydrothermal fields was estimated to be 8.5 t year –1 .…”
Section: Introductionmentioning
confidence: 99%
“…The important factor for Hg concentrations in forest soils is the time since standreplacing fires have occurred, and high soil burn severity has the potential to reduce the concentrations of Hg in burned soils for tens to hundreds of years [53,54]. In a specific emission source in Nisyros Island (Greece), Hg concentrations in fumarolic gases in Nisyros Island (Greece) ranged from 10,500 to 46,300 ng/m 3 , while Hg concentrations in the air ranged from high background values in the Lakki Plain caldera (10-36 ng/m 3 ) up to 7100 ng/m 3 in the fumarolic areas [55].…”
Section: Volcanoesmentioning
confidence: 99%